Enhanced superoxide anion release from phagocytes by muramyl dipeptide or lipopolysaccharide. - Kaku, M (1983)
Muramyl dipeptide (MDP) and lipopolysaccharide (LPS) from Escherichia coli were tested for the ability to influence superoxide anion (O2-) release from guinea pig phagocytes. Both MDP and LPS alone did not, by themselves, stimulate O2- release by macrophages and polymorphonuclear leukocytes. However, the preincubation of macrophages with MDP or LPS primed the macrophages to release an enhanced amount of O2- when stimulated by cytochalasin E and wheat germ agglutinin. When polymorphonuclear leukocytes were treated in the same way, only LPS showed an enhancing effect. MDP enhanced NADPH oxidase activity of macrophages, which is probably the reason for enhanced O2- release by MDP.